A comparative study on self medication practices in ACSR Government medical college in Nellore, India - Penupothu, Sree Nagamani; Hanumanthu, Lalitha (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Self medication is rampant in medical undergraduates. There is a need to evaluate the extent and factors that govern self medication. This study was conducted in 7th semester and 5th semester undergraduates to compare the knowledge, attitude and practice regarding self medication. Methods: It is a questionnaire based study in a total of 294 medical students comprising 147 students each belonging to 7th and 5th semesters to assess determinants and practice methods of self medication in the past one year. Results: 100% of 7th semester and 90% of 5th semester students self medicated. Majority followed modern medicine. Awareness of OTC drugs, essential drugs and generic drugs was not optimum. Students self medicated based on old prescriptions and text books for perceived mild illnesses like common cold, fever and headache. Non steroidal anti-inflammatory drugs and antihistamines were most commonly used. Not all students checked package insert prior to use. Conclusions: Self medication practice is more pronounced in 7th semester than in 5th semester students. 7th semester students used diverse drugs compared to 5th semester students who used limited groups of drugs.